A new Arum species (Areae, Araceae) from NE Turkey and Georgia - Wolfram, Lobin; Michael, Neumann; Josef, Bogner; Boyce, P.C (BGBM Berlin-Dahlem., 2007)
Arum megobrebi is described as a new species of A. subg. Arum from NE Turkey and central S Georgia and illustrated. It takes to 29 the number of species currently recognised for the genus. It is closely related to but easily distinguished from A. maculatum by, in particular, its elongate-cylindrical appendix of the spadix.